Ethnobotany, Cytotoxicity and Color Stability of Karen Natural Colorants - Sukhumaabhorn Kaewsangsai; Prateep Panyadee; Aussara Panya; Hataichanok Pandith; Prasit Wangpakapattanawong; Henrik Balslev; Angkhana Inta (Plants)
Historically, natural pigments have been used to color textiles, food, and cosmetics, but the rise of synthetic dyes in the 19th century reduced their use. Recently, interest in plant-based pigments has surged due to health and environmental concerns. Among Thailand’s ethnic groups, the Karen use plant colorants extensively, but their practices remain understudied. In this study, we document the knowledge of plant colorants of the Karen community in Chiang Mai province, assess the color stability of the plant colorants, and evaluate their cytotoxicity in HepG2 cells. Interviews with 113 informants revealed 52 plant species used for dyeing, primarily through hot water extraction. The most common color was brown, and Strobilanthes cusia had the highest color use value (0.93). The study identified 10 color shades, with blue showing the highest consensus. Color stability was tested at room and elevated temperatures, which showed that colorants from Oroxylum indicum were the most stable, and those of Strobilanthes cusia had the lowest toxicity (CC50 = 994.1 µg/mL), while Artocarpus lacucha had the highest toxicity (CC50 = 63.96 µg/mL). Oroxylum indicum, which has excellent color stability and moderate cytotoxicity (CC50 = 294.4 µg/mL), is recommended as a promising natural colorant. This study provides valuable insights into preserving traditional knowledge in Karen communities.